An enigmatic Arthropoda from the Upper Triassic (Carnian) southwestern Gondwana (Argentina). (March 2020) - Lara, María B.; Cariglino, Bárbara; Zavattieri, Ana M.; Zacarías, Iracema
Abstract: The presence of a new taxon, Duraznovis gallegoi new genus new species is reported and described from an early Late Triassic (Carnian) deposit in Argentina. Two specimens, recovered from the Quebrada del Durazno locality, uppermost levels of the Potrerillos Formation, Cuyana Basin (Mendoza), are represented by the molds of their shield and imprints of soft parts. The identity of these specimens appears enigmatic but closely resembles in the possession of a generalized arthropod morphology and a distinctive combination of characters, to living and fossil representatives of xiphosurans (Chelicerata) and notostracans (Branchiopoda). The new fossils are associated with a rich biota comprising abundant insects, spinicaudatans, plants, and scarce fish remains living in semipermanent swamps and/or ponds within a delta plain environment with intermittent episodes of flooding, in a warm temperate and humid megamonsoonal climate during Triassic times. In this context, we analyze the taphonomic and ecological implications of their presence. Lastly, these unique specimens at the Quebrada del Durazno locality adds to the diversity of the biota, revealing the importance of this site as an exceptional paleontological Triassic deposit. UUID: http://zoobank.org/8d1194c2-170c-4b7a-b0c6-5c08b0974d95